2015
DOI: 10.33320/maced.pharm.bull.2015.61.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oligofructose-enriched inulin on survival of microencapsulated Lactobacillus casei 01 and adhesive properties of synbiotic microparticles

Abstract: Lactobacillus casei 01 was co-encapsulated with the prebiotic oligofructose-enriched inulin at different concentrations to investigate the efficiency of the prebiotic for improving the probiotic viability. Prebiotic effect on the probiotic survival under microencapsulation conditions by spray- and freeze-drying and storage stability of encapsulated living cells at 4 °C during period of 8 weeks was evaluated. Adhesiveness of L. casei 01 loaded microparticles to pig mucin was investigated in vitro to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Krasaekoopt and Watcharapoka (2014) suggested that the addition of prebiotics during microencapsulation was not only providing better protection to probiotics, but also enhancing the growth of these microorganisms in simulated digestive system. On the other hand, some authors reported that the increase concentration of oligofructose-enriched inulin from 1.5 to 5% w/w did not provide the increase in cell survival or insignificantly improved the survival rate during the spray-and freezedrying processes (Ivanovska, Zhivikj, Mladenovska, & Petrushevska-Tozi, 2015).…”
Section: The Effect Of Different Prebiotic Concentration On Microcapsulementioning
confidence: 99%
See 1 more Smart Citation
“…Krasaekoopt and Watcharapoka (2014) suggested that the addition of prebiotics during microencapsulation was not only providing better protection to probiotics, but also enhancing the growth of these microorganisms in simulated digestive system. On the other hand, some authors reported that the increase concentration of oligofructose-enriched inulin from 1.5 to 5% w/w did not provide the increase in cell survival or insignificantly improved the survival rate during the spray-and freezedrying processes (Ivanovska, Zhivikj, Mladenovska, & Petrushevska-Tozi, 2015).…”
Section: The Effect Of Different Prebiotic Concentration On Microcapsulementioning
confidence: 99%
“…They suggested that encapsulation technique with double coating material such as chitosan may provide better protection for probiotic from frozen damage during freeze-drying process. Ivanovska et al (2015) showed that the viability of co-encapsulate L. casei 01 in chitosan-Ca-alginate microparticles in the presence of oligofructose-enriched inulin after freeze-drying was significantly increased when compared to the formulation without prebiotic. Abbaszadeh, Gandomi, Misaghi, Bokaei, and Noori (2014) found that the combination with 2% and 3% alginate and increasing the chitosan concentration from 0.2% to 1% to coat alginate gel induced a significant increase in gastric survival rate of L. rhamnosus GG.…”
Section: The Effect Of Different Chitosan Concentration On Microcapsulementioning
confidence: 99%